Evaluation in Physical Education Learning for Mentally Retarded Students during the Covid-19 Pandemic - Akhmad Olih Solihin (Universitas Pendidikan Indonesia, 2022)
This study aimed to determine the implementation of evaluation in Physical Education, Sports, and Health learning during Covid-19 Pandemic at a Special Need School in Cimahi City. This research is descriptive research. The method used was a survey method using a questionnaire for collecting data. The subjects of this study were all teachers of mentally retarded students at a Special Need School in Cimahi City, including 11 teachers, selected through a total sampling technique. The instrument used was a close ended questionnaire. The data analysis technique used quantitative descriptive analysis stated in percentages. The results of the survey of the implementation of evaluation in PJOK learning at a Special Need School in Cimahi City included 0% (0 teachers) in the